Factors influencing the consumption of seafood among young children in Perth: a qualitative study - Howat Peter A; Burns Sharyn K; McManus Alexandra; Cooper Lisa; Fielder Lynda (BMC, 2007)
Abstract Background This formative study sought to explore the factors that influence the consumption of fish and seafood among 4-6 year old children in the Perth metropolitan area. Focus groups were conducted with mothers of young children to gain insights into the enablers and barriers to regular seafood consumption in children, and the knowledge, attitudes and perceptions of their mothers to including seafood as a regular part of their children's diet. Methods Purposive sampling techniques were used to select and recruit mothers of children aged between four and six years from within the Perth metropolitan area. A total of seven focus groups were conducted. Thematic content analysis was employed to code data generated and to extract major themes. Results Findings indicated that all children of study participants had tried fish and seafood products, with some being exposed to a wide variety from an early age. Across focus groups, several dominant factors were apparent in influencing the frequency and type of seafood purchased and consumed. Perceived cost, freshness, availability/accessibility, and the level of confidence to prepare a meal to suit all family members were significant determinants of whether seafood featured regularly on the household menu. The influence of others in the family (particularly the husband or partner) also tended to impact upon the likelihood of serving fish and seafood, and the types of products mothers were willing to serve. Conclusion Findings from this qualitative study indicate that interventions seeking to promote seafood (particularly fish) as an integral part of a healthy diet should address existing negative attitudes and beliefs around the storage and preparation of seafood. The influence of dominant male influences within the family unit should also be considered. Strategies directed at parents and children should include experimental 'hands-on' components to encourage experimentation, particularly focussing on ease of preparation and the variety of lower cost seafood available.